2015
DOI: 10.2139/ssrn.2704399
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Islam in West European Societies - An Investigation of Different Concepts of Religious Re-Affiliation

Abstract: The Robert Schuman Centre for Advanced Studies (RSCAS), created in 1992 and directed by Professor Brigid Laffan, aims to develop inter-disciplinary and comparative research on the major issues facing the process of European integration, European societies and Europe's place in 21 st century global politics. The Centre is home to a large post-doctoral programme and hosts major research programmes, projects and data sets, in addition to a range of working groups and ad hoc initiatives. The research agenda is org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…An important consideration for this study is that it is difficult to say whether our sample is representative of the population of Muslim converts in the United States. There are little reliable data available on the number and demographics of Muslim converts in Europe, where Islam has been extensively studied (Uhlmann, 2015), and there are even less data available regarding the demographics of the Muslim convert population in the United States. One of the few studies to collect data on United States Muslim converts (Evans, 2015) reported similar racial demographics to those found in our sample, but had a much greater proportion of individuals with graduate degrees (about 3 times as many) than our sample and the overall United States Muslim population, suggesting sampling bias in that study.…”
Section: Discussionmentioning
confidence: 99%
“…An important consideration for this study is that it is difficult to say whether our sample is representative of the population of Muslim converts in the United States. There are little reliable data available on the number and demographics of Muslim converts in Europe, where Islam has been extensively studied (Uhlmann, 2015), and there are even less data available regarding the demographics of the Muslim convert population in the United States. One of the few studies to collect data on United States Muslim converts (Evans, 2015) reported similar racial demographics to those found in our sample, but had a much greater proportion of individuals with graduate degrees (about 3 times as many) than our sample and the overall United States Muslim population, suggesting sampling bias in that study.…”
Section: Discussionmentioning
confidence: 99%
“…The orient, states Said (1979), was made orient as it was imagined (p. 6). West has been powerful to represent and depict Islam, argues Uhlmann (2015), which is why violence is associated with the term Muslim fundamentalism.…”
Section: Introductionmentioning
confidence: 99%